PENGARUH KONTEN MARKETING, INFLUENCER MARKETING, CUSTOMER REVIEW TERHADAP MINAT BELI PRODUK MAKEUP DAN SKINCARE SKINTIFIC PADA TOKO MISSGLAM KOTA BENGKULU - Syahcika Aritia Agripina (UM. Bengkulu, 2026)
Public interest in beauty products, particularly makeup and skincare, continues to grow alongside technological advancements and the increasing use of social media. This study aims to analyze the influence of content marketing, influencer marketing, and customer reviews on purchase intention for Skintific products at MissGlam Store in Bengkulu City. Data were collected from 180 consumers through a questionnaire and analyzed using multiple linear regression. The results show that content marketing has a positive and significant effect on purchase intention. This means that the more attractive, informative, and relevant the content, the higher the consumer's interest in purchasing the product. Influencer marketing also has a positive and significant impact, indicating that the credibility and appeal of influencers play a role in driving purchase decisions. In contrast, customer reviews do not have a significant effect on purchase intention, suggesting that a large number of positive reviews does not necessarily increase consumers' desire to buy the product. These findings indicate that content-based marketing strategies and the use of influencers are more effective in increasing purchase intention. Therefore, businesses should manage customer reviews more strategically to enhance their impact on consumer purchasing decisions. Keywords: Content Marketing, Influencer Marketing, Online Customer Review, Purchase Intention